KERJA SAMA ORANGTUA DAN WALI BAPTIS DALAM PENDIDIKAN IMAN ANAK - Samantha, Margaretha Eka Septiana; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2022)
This study aims to analyze parents' understanding of the duties and responsibilities in children's faith education, to find out godparents' understanding of the duties and responsibilities in children's faith education, and how parents and godparents collaborate in children's faith education at the Immaculate Conception Parish in Surabaya. This study uses a qualitative method. The results of the study indicate that parents and godparents understand the duties and responsibilities in children's faith education and carry them out in various concrete actions based on the five tasks of the church, there has been cooperation between parents and godparents in fostering children's faith.